Innovative and Competitive Potential of Targeted Effectiveness Foods - A. M. Marhunova; S. A. Kondratenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides key trends of developing food industry in the world, shows approaches to supporting innovation lines in academic research in the EU and other countries with high level of food security. Theoretical and methodological aspects of the innovative potential and competition in enriched and specialty foods are discussed. The authors show the necessity to develop and introduce scientifically grounded methodology and information support of analyzing, evaluating and forecasting the competitiveness of manufacturers and certain types of produce, which take into account the dynamic development of technologies and innovation on market of enriched and specialty produce and steps aimed at improving the product properties and rational satisfaction of customer preferences. The authors substantiate principles of effective innovation development of enterprises of food industry, including complex realization of innovative potential, detailed and systematic use of all types of innovation, optimization of material and labour use, stable access of economic entities to market data and results of marketing research, guarantee of physical and price accessibility of innovation foods for all categories of the population. Principle mechanisms of their implementation are grounded on the basis of strategic partnership between entities in the technological chain of developing foods of high quality.